2020
DOI: 10.15252/embr.201949863
|View full text |Cite
|
Sign up to set email alerts
|

The 18S rRNA m 6 A methyltransferase METTL 5 promotes mouse embryonic stem cell differentiation

Abstract: RNA modifications represent a novel layer of regulation of gene expression. Functional experiments revealed that N 6-methyladenosine (m 6 A) on messenger RNA (mRNA) plays critical roles in cell fate determination and development. m 6 A mark also resides in the decoding center of 18S ribosomal RNA (rRNA); however, the biological function of m 6 A on 18S rRNA is still poorly understood. Here, we report that methyltransferase-like 5 (METTL5) methylates 18S rRNA both in vivo and in vitro, which is consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
67
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 60 publications
4
67
1
Order By: Relevance
“…Notably, the knockdown of Ddx21 phenocopies the depletion of Aes by reducing growth capacity of leukemia cells [23]. Other modifications in rRNAs, such as m 6 A and m 5 C, have been recently linked to ribosome function, stem cell differentiation, and cancer [27][28][29][64][65][66][67]. In particular, 18S and 28S rRNAs contain two m 6 A methylations at position A1832 and A4220, respectively.…”
Section: Rrna Modificationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, the knockdown of Ddx21 phenocopies the depletion of Aes by reducing growth capacity of leukemia cells [23]. Other modifications in rRNAs, such as m 6 A and m 5 C, have been recently linked to ribosome function, stem cell differentiation, and cancer [27][28][29][64][65][66][67]. In particular, 18S and 28S rRNAs contain two m 6 A methylations at position A1832 and A4220, respectively.…”
Section: Rrna Modificationsmentioning
confidence: 99%
“…However, both studies found that METTL5 was required for correct differentiation. Furthermore, the lack of m 6 A in 18S rRNA was found to affect the translation of specific mRNAs [28]. Translation of Fbxw7 (F-box and WD repeat domain-containing protein 7), a protein involved in the degradation of c-MYC, was found to be specifically regulated by 18S rRNA m 6 A modification and to play an important role in mESC differentiation [28].…”
Section: Rrna Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…MettL5 forms a heterodimer with Trm112, a conserved protein that binds to and stabilizes various MTase proteins and was named initially for its role in tR NA m ethylation ( 29 , 30 ). The MettL5-Trm112 complex is responsible for 18S rRNA adenine methylation at position 1832 ( 31 , 32 , 33 , 34 , 35 ). Finally, MettL16 catalyzes adenine methylation in the conserved sequence UAC A GAGAA, within hairpins in the 3′ UTR of the SAM synthetase (MAT2A) mRNA and in U6 snRNA ( 36 , 37 , 38 ).…”
mentioning
confidence: 99%